Кібербезпека в мережах 5G - Пастушенко, М. С.; Сазонов, Б. О. (ХНУРЕ, 2023)
Cyber security in 5G networks is an important issue in the context of the development and implementation of a new generation of mobile networks. 5G networks provide significant bandwidth, low latency, and support for a large number of connected devices, making them attractive for a variety of applications, including the Internet of Things (IoT), autonomous cars, and other innovative technologies. But these new capabilities also create new cyber threats. Cybercriminals can use 5G networks to launch new kinds of attacks, including high-bandwidth DDoS attacks, IoT device security attacks, and more.
Keywords: кібербезпека; мережа 5G